A super-fouling-resistant three-dimensional transparent glaze and its preparation process
Through modified kaolin and multi-process treatment, an ultra-stainless three-dimensional permeable gloss is prepared, which solves the problem of reduced gloss and insufficient stain resistance when dealing with invisible stains in existing glosses, and achieves high stain resistance and aesthetics of gloss.
Patent Information
- Application Number
- CN202411259060.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-09-10
AI Technical Summary
When existing ceramic tile glaze deals with stains that are invisible to the naked eye, it is difficult to maintain gloss and aesthetics, and it is not stain-resistant enough.
An ultra-foul-resistant three-dimensional permeable glaze is adopted, which includes base glaze and ultra-foul-resistant surface glaze. Through technical means such as modification of kaolin, ball milling, microwave radiation and baking treatment, the stain resistance and gloss of the glaze are improved.
It achieves the glaze with super stain resistance, smooth and beautiful appearance, strong three-dimensional sense, corrosion resistance and wear resistance, and at the same time expands the firing range and enhances the decorative effect of the product.
Smart Images

Figure CN119019093B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of glaze preparation, and relates to a super-fouling-resistant three-dimensional transparent glaze and a preparation process thereof. Background Art
[0002] As a decorative material that beautifies living spaces, architectural ceramic tiles are widely used in the home decoration industry and have also undergone significant changes. With the development of industry, the dirt absorption of tiles is the most difficult problem to solve. Visible stains on the surface of tiles can be scrubbed clean, but some stains that are invisible to the naked eye will affect the gloss or whiteness of the tiles over time, reducing the aesthetics of the tiles.
[0003] The invention discloses a super-fouling-resistant three-dimensional transparent glaze preparation process and method, which has a leap-forward improvement in terms of stain resistance. The invention ensures the super-fouling-resistant effect while having the functions of being smooth and beautiful, having a stronger and more realistic three-dimensional sense, being corrosion-resistant, wear-resistant, having a wide firing range, and being able to increase the decorative effect of the product. Summary of the invention
[0004] The purpose of the present invention is to provide a super-fouling-resistant three-dimensional transparent glaze and a preparation process thereof, which has the characteristics of being resistant to dirt and wear.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A super-fouling-resistant three-dimensional transparent glaze, comprising a base glaze and a super-fouling-resistant top glaze, wherein the base glaze has the following formula: by mass percentage, nepheline 10-25%, albite 10-15%, kaolin 5-10%, ball clay 2-5%, calcined alumina 10-15%, quartz 15-20%, potassium feldspar 15-25%, dolomite 2-4%, talc 2-5%, zinc oxide 3%;
[0007] The formula of the super stain-resistant glaze is as follows: by mass percentage, 40-45% high-temperature frit, 30-40% quartz, 3-5% strontium carbonate, 3-5% zinc oxide, 10-15% modified kaolin, and 3-5% aluminum oxide;
[0008] The preparation method of modified kaolin is as follows:
[0009] S1.1: kaolin and silicon carbide were mixed in a mass ratio of 4:1, and ground in a ball mill at a speed of 300 r / min for 1 h to obtain a mixture A;
[0010] S1.2: Dimethyl sulfoxide and dimethylformamide were mixed in a mass ratio of 2:1, and 2 wt% potassium acetate was added, and the mixture was stirred to obtain a mixed solution B. The mixture A was dispersed in the mixed solution B to obtain a solid-liquid mixture C with a mass fraction of 30%. After ultrasonic treatment for 0.5 h, the mixture was filtered to obtain a mixture D;
[0011] S1.3: subjecting the mixture D to microwave radiation for 5 min at a microwave frequency of 600 MHz to obtain a mixture E;
[0012] S1.4: Transfer the mixture E to a muffle furnace and heat it from room temperature to 1000°C for calcination for 3 hours. After calcination, slowly cool it to room temperature, crush and sieve it to obtain a 150-mesh solid powder, which is the modified kaolin.
[0013] Furthermore, the composition of the high-temperature frit is Al2O3: 23.58%, SiO2: 45.47%, CaO: 16.61%, MgO: 0.45%, BaO: 1.33%, Na2O: 1.07%, K2O: 4.74%, and ZnO: 6.75%.
[0014] Furthermore, the heating rate in S1.4 is 5°C / min.
[0015] Furthermore, the rate of slowly cooling to room temperature in S1.4 is 3°C / min.
[0016] A preparation process of a super-fouling-resistant three-dimensional transparent glaze, the specific process of the preparation process of the super-fouling-resistant three-dimensional transparent glaze is as follows:
[0017] S5.1: Put the raw materials of the base glaze into a ball mill according to the formula ratio, the speed of the ball mill is 300r / min, after grinding for 1h, add 35wt% of water, 0.1wt% of sodium carboxymethyl cellulose and 0.45wt% of sodium tripolyphosphate, increase the speed of the ball mill to 400r / min, continue grinding for 8h, use a magnetic iron remover to remove iron, and obtain the base glaze E;
[0018] S5.2: Put the raw materials of the super stain-resistant glaze into a ball mill according to the formula ratio, the speed of the ball mill is 300r / min, after grinding for 1h, add 35wt% of water, 0.1wt% of sodium carboxymethyl cellulose and 0.45wt% of sodium tripolyphosphate, increase the speed of the ball mill to 400r / min, continue grinding for 8h, use a magnetic iron remover to remove iron, and obtain super stain-resistant glaze F;
[0019] S5.3: The surface of the green body is purged with nitrogen, and the base glaze E is poured on the surface of the green body by the pouring method. After the pouring is completed, it is allowed to stand and dry to obtain a green body G;
[0020] S5.4: spraying pigment onto the surface of body G, and letting it stand to dry again to obtain body H;
[0021] S5.5: pouring the super stain-resistant glaze F on the surface of the body H by a pouring method, and letting it stand to dry after pouring to obtain the body I;
[0022] S5.6: placing the body I into a kiln for firing at a kiln temperature of 1140° C. for a firing cycle of 50 min. cooling to room temperature after firing, and polishing to obtain the ultra-fouling-resistant three-dimensional transparent glaze.
[0023] Furthermore, the purge flow rate of nitrogen in S5.3 is 10 m / s.
[0024] Furthermore, the parameters of the glazing method in S5.3 are: glazing distance 30 cm, base glaze specific gravity 1.82-1.88 g / ml, glazing amount 60 g / piece, and tile size 300*600 mm.
[0025] Furthermore, the spraying parameters of the pigment in S5.4 are: spraying distance 80 mm, spraying rate 60 mm / s.
[0026] Furthermore, the parameters of the glazing method in S5.5 are: glazing distance 30 cm, specific gravity of super stain-resistant glaze 1.82-1.87 g / ml, glazing amount 70 g / piece, and tile size 300*600 mm.
[0027] Furthermore, the polishing steps described in S5.6 are carried out in sequence using the following grinding heads, grinding heads composed of 5 groups of 150-mesh elastic modules, grinding heads composed of 5 groups of 600-mesh elastic modules, grinding heads composed of 5 groups of 800-mesh elastic modules, grinding heads composed of 4 groups of 1000-mesh elastic modules, grinding heads composed of 4 groups of 1200-mesh elastic modules, grinding heads composed of 5 groups of 1500-mesh elastic modules and grinding heads composed of 4 groups of 2000-mesh elastic modules. The pressure applied to the surface of the ceramic tiles by the grinding heads composed of the elastic modules is 1.3 to 2.0 MPa.
[0028] The role of the high-temperature frit in the super-fouling resistant glaze formula is to improve the melting performance of the formula, make the glaze layer denser when melted at high temperature, the bubbles in the glaze layer are discharged more cleanly, and the pores are better. The role of quartz in the formula is to improve the mechanical strength of the glaze and make it more transparent. The role of strontium carbonate in the formula is to have a stronger fluxing effect and good color. The role of zinc oxide in the formula is to increase the firing range of the glaze and also to improve the transparency of the glaze. Kaolin can improve the suspension of the glaze slurry to prevent precipitation, and can also increase the aluminum content of the formula. Alumina in the formula mainly improves the wear resistance of the formula, improves the mechanical strength of the glaze, and increases the refractoriness of the glaze.
[0029] The present invention modifies kaolin by using an intercalation modifier to increase the interlayer distance of kaolin, increase the specific surface area, and improve the adsorption performance.
[0030] First, kaolin and silicon carbide are mixed and ground to a certain fineness by a ball mill so that the two are fully mixed and evenly dispersed, which helps to uniformly carry out the chemical reaction in the subsequent steps and improve the uniformity of the glaze layer;
[0031] Dispersing the mixture in a mixed solution and subjecting it to ultrasonic treatment can help further refine the particles and promote uniform dispersion of the particles in the solution, which is conducive to forming a smoother and denser glaze layer. At the same time, dimethyl sulfoxide, dimethylformamide and potassium acetate can also interact with kaolin as solvents and intercalants. In this process, penetration and insertion of solvent molecules into the interlayers of kaolin will occur. Organic solvents such as dimethyl sulfoxide, dimethylformamide and potassium acetate usually have smaller molecular sizes and appropriate polarity, and can directly enter the interlayers of kaolin through the destruction and reconstruction of interlayer hydrogen bonds.
[0032] The molecular structure of dimethyl sulfoxide allows it to be smoothly inserted into the kaolin interlayer by destroying the hydrogen bonds between kaolin layers, mainly because the S and O elements in its molecules interact with kaolin and form new bonds with the hydroxyl groups on its inner surface; dimethylformamide can also be inserted by directly destroying the hydrogen bonds between kaolin layers and forming new interactions with them, mainly because the C, N and O elements in its molecules participate in the interaction; potassium acetate usually forms hydrogen bonds with the hydroxyl group (-OH) of the aluminum oxide layer of kaolinite or the oxygen (O) of the silicon oxide layer through its functional group C=O, thereby achieving insertion, mainly because the K, C and O elements in its molecules interact with kaolin.
[0033] The intercalant molecules form hydrogen bonds with the hydroxyl or oxygen atoms on the surface of the interlayer domain of kaolin and stably exist between the layers. The insertion of the intercalant increases the interlayer distance, thereby changing the surface properties of kaolin.
[0034] The intercalated kaolin has better dispersion in the glaze, which helps to form a uniform glaze surface; the intercalated structure enhances the interaction between kaolin and the glaze, improving the adhesion and durability of the glaze surface; the intercalated modification changes the surface energy of kaolin, thereby improving the glaze surface's stain resistance, glossiness, hardness and other properties.
[0035] Microwave radiation quickly heats the mixture and promotes chemical reactions, which helps to form more stable chemical bonds and phase change products, improve the hardness and wear resistance of the glaze layer, and in addition, microwave radiation promotes the intercalation reaction. Microwave heating is fast and uniform, which can accelerate the evaporation of the solvent and the diffusion of the intercalation agent. Under microwave radiation, the intercalation agent can be more deeply inserted into the kaolin interlayer to form a more stable intercalation structure.
[0036] The roasting process removes impurities such as organic matter and moisture and promotes the sintering process between inorganic substances, which helps the modified kaolin to form a denser glaze layer and improve the hardness and gloss of the glaze when preparing glaze.
[0037] The surface structure and chemical properties of modified kaolin are changed through surface modification treatment, which enhances the bonding force with the glaze, thereby improving the density and permeability resistance of the glaze and effectively preventing the penetration and adhesion of stains. The addition of silicon carbide and subsequent solution intercalation modification combined with microwave radiation and roasting treatment make the crystal structure of the modified kaolin more stable and the hardness increased, thereby enhancing the wear resistance and scratch resistance of the glaze. The grinding and dispersion process makes the kaolin particles more evenly distributed. Ultrasonic treatment further promotes the refinement of the particles, which is conducive to forming a smoother glaze and improving the gloss of the glaze. The addition of solvents makes the glaze more stable and not easy to stratify or precipitate, which is conducive to construction and the formation of a uniform glaze layer.
[0038] The present invention firstly ensures the uniformity and fineness of the glaze composition through a ball milling process, including speed adjustment at different stages and long-term grinding, which is conducive to the uniform coating of the glaze and improves the density and flatness of the glaze layer; in the process of preparing the glaze, 35wt% of water, 0.1wt% of sodium carboxymethyl cellulose and 0.45wt% of sodium tripolyphosphate are added as additives. These additives help to improve the rheology and stability of the glaze, making the glaze smoother during the spraying process and reducing the generation of bubbles and defects; a magnetic iron remover is used to remove iron from the glaze, effectively removing iron impurities in the glaze. The color spots and defects caused by iron oxidation in the glaze layer during the firing process are effectively avoided, and the smoothness and aesthetics of the glaze layer are improved.
[0039] Nitrogen purging on the surface of the green body can remove dust and impurities on the surface, providing a clean surface for the subsequent glazing process. This helps to enhance the bonding between the glaze layer and the green body, and improve the adhesion and durability of the glaze layer. The base glaze and the top glaze are poured on the surface of the green body in sequence using the pouring glaze method. This method ensures that the glaze layer is evenly coated and avoids uneven thickness or missing glaze layers. At the same time, the glaze layer is fully solidified through the static drying process, laying a good foundation for subsequent processing and firing.
[0040] The green body is placed in a kiln for firing at 1140°C for 50 minutes. This temperature and duration can ensure that the glaze is fully melted and tightly combined with the green body to form a dense glaze layer. The surface glossiness of the fired product is 80-100°. At the same time, this temperature and duration can also help reduce defects such as bubbles and cracks in the glaze layer. After firing, it is cooled to room temperature and polished. Polishing can further improve the smoothness and aesthetics of the glaze layer and make the glaze surface smoother and more delicate. At the same time, polishing can also help remove tiny defects and scratches on the surface of the glaze layer and improve the overall quality of the product. The surface glossiness of the present invention after polishing is 100-105°.
[0041] Beneficial effects of the present invention:
[0042] The present invention modifies kaolin, and through surface modification treatment, the surface structure and chemical properties of kaolin are changed, the bonding force with glaze is enhanced, thereby improving the compactness and permeability resistance of the glaze surface, effectively preventing the penetration and adhesion of stains, and the addition of silicon carbide and subsequent solution intercalation modification combined with microwave radiation and roasting treatment make the crystal structure of the modified kaolin more stable, the hardness is improved, and the wear resistance and scratch resistance of the glaze surface are enhanced. The grinding and dispersion process makes the kaolin particles more evenly distributed, and the ultrasonic treatment further promotes the refinement of the particles, which is conducive to forming a smoother glaze surface and improving the glossiness of the glaze surface. The addition of solvent makes the glaze more stable, not easy to be delaminated or precipitated, and is conducive to construction and forming a uniform glaze layer.
[0043] The present invention ensures the uniformity and fineness of glaze components and the uniform coating of glaze by ball milling, improves the density and flatness of glaze layer, adds water, sodium carboxymethyl cellulose and sodium tripolyphosphate as additives to improve the rheology and stability of glaze, makes the glaze smoother during spraying, and then uses magnetic iron remover to remove iron from glaze, effectively avoids color spots and defects caused by iron oxidation in glaze layer during firing, and improves the smoothness and aesthetics of glaze layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] In order to facilitate understanding by those skilled in the art, the present invention is further described below with reference to the accompanying drawings.
[0045] Figure 1 The glaze effect diagram of the super-fouling-resistant three-dimensional transparent glaze prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0046] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation method, structure, characteristics and effects of the present invention are described in detail below in conjunction with the accompanying drawings and preferred embodiments.
[0047] Base glaze formula ratio 1: nepheline 15%, albite 12%, kaolin 5%, ball clay 5%, calcined alumina 15%, quartz 15%, potassium feldspar 25%, dolomite 2%, talc 3%, zinc oxide 3%;
[0048] Base glaze formula ratio 2: nepheline 10%, albite 15%, kaolin 10%, ball clay 3%, calcined alumina 15%, quartz 20%, potassium feldspar 15%, dolomite 4%, talc 5%, zinc oxide 3%;
[0049] Base glaze formula ratio 3: nepheline 25%, albite 10%, kaolin 10%, ball clay 2%, calcined alumina 10%, quartz 15%, potassium feldspar 20%, dolomite 2%, talc 3%, zinc oxide 3%;
[0050] Super stain-resistant glaze formula ratio 1: high-temperature frit 45%, quartz 30%, strontium carbonate 5%, zinc oxide 5%, modified kaolin 10%, aluminum oxide 5%;
[0051] Super stain-resistant glaze formula ratio 2: high-temperature frit 45%, quartz 30%, strontium carbonate 4%, zinc oxide 3%, modified kaolin 15%, aluminum oxide 3%;
[0052] Super stain-resistant glaze formula ratio 3: high-temperature frit 40%, quartz 40%, strontium carbonate 3%, zinc oxide 3%, modified kaolin 10%, aluminum oxide 4%;
[0053] The preparation method of modified kaolin is as follows:
[0054] S1.1: kaolin and silicon carbide were mixed in a mass ratio of 4:1, and ground in a ball mill at a speed of 300 r / min for 1 h to obtain a mixture A;
[0055] S1.2: Dimethyl sulfoxide and dimethylformamide were mixed in a mass ratio of 2:1, and 2 wt% potassium acetate was added, and the mixture was stirred to obtain a mixed solution B. The mixture A was dispersed in the mixed solution B to obtain a solid-liquid mixture C with a mass fraction of 30%. After ultrasonic treatment for 0.5 h, the mixture was filtered to obtain a mixture D;
[0056] S1.3: subjecting the mixture D to microwave radiation for 5 min at a microwave frequency of 600 MHz to obtain a mixture E;
[0057] S1.4: Transfer the mixture E to a muffle furnace and heat it from room temperature to 1000°C for calcination at a heating rate of 5°C / min for 3 hours. After calcination, slowly cool it to room temperature at a rate of 3°C / min. Grind and sieve to obtain a 150-mesh solid powder, which is the modified kaolin.
[0058] Among them, the composition of the high-temperature sintered block is Al2O3: 23.58%, SiO2: 45.47%, CaO: 16.61%, MgO: 0.45%, BaO: 1.33%, Na2O: 1.07%, K2O: 4.74%, and ZnO: 6.75%.
[0059] Example 1
[0060] S5.1: Put the ingredients of the base glaze into a ball mill according to the base glaze formula ratio 1, the speed of the ball mill is 300r / min, after grinding for 1h, add 35wt% of water, 0.1wt% of sodium carboxymethyl cellulose and 0.45wt% of sodium tripolyphosphate, increase the speed of the ball mill to 400r / min, continue grinding for 8h, use a magnetic iron remover to remove iron, and obtain base glaze E;
[0061] S5.2: Put the ingredients of the super-fouling resistant glaze into a ball mill according to the super-fouling resistant glaze formula ratio 1, the ball mill speed is 300r / min, after grinding for 1h, 35wt% of water, 0.1wt% of sodium carboxymethyl cellulose and 0.45wt% of sodium tripolyphosphate are added, the ball mill speed is increased to 400r / min, and grinding is continued for 8h. The magnetic iron remover is used to remove iron to obtain the super-fouling resistant glaze F;
[0062] S5.3: The surface of the green body is purged with nitrogen at a nitrogen purging flow rate of 10 m / s. The base glaze E is first poured on the surface of the green body by the pouring method. The pouring distance is 30 cm, the base glaze specific gravity is 1.85 g / ml, the glaze amount is 60 g / piece, and the size of the tile is 300*600 mm. After pouring, it is left to dry to obtain a body G;
[0063] S5.4: spraying pigment onto the surface of the body G, the spraying parameters of the pigment are spraying distance 80 mm, spraying rate 60 mm / s, and standing to dry again to obtain the body H;
[0064] S5.5: pour the super stain-resistant glaze F on the surface of the body H by pouring glaze method, the pouring distance is 30 cm, the specific gravity of the super stain-resistant glaze is 1.85g / ml, the glaze amount is 70g / piece, the size of the brick is 300*600mm, after pouring, let it stand and dry to obtain the body I;
[0065] S5.6: placing the body I into a kiln for firing at a kiln temperature of 1140° C. for a firing cycle of 50 min. cooling to room temperature after firing, and polishing to obtain the ultra-fouling-resistant three-dimensional transparent glaze.
[0066] Among them, the polishing steps described in S5.6 are carried out in sequence using the following grinding heads, grinding heads composed of 5 groups of 150-mesh elastic modules, grinding heads composed of 5 groups of 600-mesh elastic modules, grinding heads composed of 5 groups of 800-mesh elastic modules, grinding heads composed of 4 groups of 1000-mesh elastic modules, grinding heads composed of 4 groups of 1200-mesh elastic modules, grinding heads composed of 5 groups of 1500-mesh elastic modules and grinding heads composed of 4 groups of 2000-mesh elastic modules. The pressure applied to the surface of the ceramic tiles by the grinding heads composed of the elastic modules is 1.8 MPa.
[0067] Example 2
[0068] S5.1: Put the ingredients of the base glaze into a ball mill according to the base glaze formula ratio 2, the speed of the ball mill is 300r / min, after grinding for 1h, 35wt% of water, 0.1wt% of sodium carboxymethyl cellulose and 0.45wt% of sodium tripolyphosphate are added, the speed of the ball mill is increased to 400r / min, and grinding is continued for 8h. The magnetic iron remover is used to remove iron to obtain the base glaze E;
[0069] S5.2: Put the ingredients of the super-fouling resistant glaze into a ball mill according to the formula ratio 2 of the super-fouling resistant glaze, the speed of the ball mill is 300 r / min, after grinding for 1 hour, 35wt% of water, 0.1wt% of sodium carboxymethyl cellulose and 0.45wt% of sodium tripolyphosphate are added, the speed of the ball mill is increased to 400r / min, and grinding is continued for 8 hours. The magnetic iron remover is used to remove iron to obtain the super-fouling resistant glaze F;
[0070] S5.3: The surface of the green body is purged with nitrogen at a nitrogen purging flow rate of 10 m / s. The base glaze E is first poured on the surface of the green body by the pouring method. The pouring distance is 30 cm, the base glaze specific gravity is 1.82 g / ml, the glaze amount is 60 g / piece, and the size of the tile is 300*600 mm. After pouring, it is left to dry to obtain a body G;
[0071] S5.4: spraying pigment onto the surface of the body G, the spraying parameters of the pigment are spraying distance 80 mm, spraying rate 60 mm / s, and standing to dry again to obtain the body H;
[0072] S5.5: pour the super stain-resistant glaze F on the surface of the body H by pouring glaze method, the pouring distance is 30 cm, the specific gravity of the super stain-resistant glaze is 1.87 g / ml, the glaze amount is 70 g / piece, the size of the brick is 300*600 mm, after pouring, let it stand and dry to obtain the body I;
[0073] S5.6: placing the body I into a kiln for firing at a kiln temperature of 1140° C. for a firing cycle of 50 min. cooling to room temperature after firing, and polishing to obtain the ultra-fouling-resistant three-dimensional transparent glaze.
[0074] Among them, the polishing steps described in S5.6 are carried out in sequence using the following grinding heads, grinding heads composed of 5 groups of 150-mesh elastic modules, grinding heads composed of 5 groups of 600-mesh elastic modules, grinding heads composed of 5 groups of 800-mesh elastic modules, grinding heads composed of 4 groups of 1000-mesh elastic modules, grinding heads composed of 4 groups of 1200-mesh elastic modules, grinding heads composed of 5 groups of 1500-mesh elastic modules and grinding heads composed of 4 groups of 2000-mesh elastic modules. The pressure applied to the surface of the ceramic tiles by the grinding heads composed of the elastic modules is 1.3 MPa.
[0075] Example 3
[0076] S5.1: Put the ingredients of the base glaze into a ball mill according to the base glaze formula ratio 3, the speed of the ball mill is 300r / min, after grinding for 1h, 35wt% of water, 0.1wt% of sodium carboxymethyl cellulose and 0.45wt% of sodium tripolyphosphate are added, the speed of the ball mill is increased to 400r / min, and grinding is continued for 8h. The magnetic iron remover is used to remove iron to obtain the base glaze E;
[0077] S5.2: Put the ingredients of the super-fouling resistant glaze into a ball mill according to the formula ratio 3 of the super-fouling resistant glaze, and the speed of the ball mill is 300 r / min. After grinding for 1 hour, 35wt% of water, 0.1wt% of sodium carboxymethyl cellulose and 0.45wt% of sodium tripolyphosphate are added, and the speed of the ball mill is increased to 400r / min. The grinding is continued for 8 hours, and the iron is removed by a magnetic iron remover to obtain a super-fouling resistant glaze F;
[0078] S5.3: The surface of the green body is purged with nitrogen at a nitrogen purging flow rate of 10 m / s. The base glaze E is first poured on the surface of the green body by the pouring method. The pouring distance is 30 cm, the base glaze specific gravity is 1.88 g / ml, the glaze amount is 60 g / piece, and the size of the tile is 300*600 mm. After pouring, it is left to dry to obtain a body G;
[0079] S5.4: spraying pigment onto the surface of the body G, the spraying parameters of the pigment are spraying distance 80 mm, spraying rate 60 mm / s, and standing to dry again to obtain the body H;
[0080] S5.5: pour the super stain-resistant glaze F on the surface of the body H by pouring glaze method, the pouring distance is 30 cm, the specific gravity of the super stain-resistant glaze is 1.82g / ml, the glaze amount is 70g / piece, the size of the brick is 300*600mm, after pouring, let it stand and dry to obtain the body I;
[0081] S5.6: placing the body I into a kiln for firing at a kiln temperature of 1140° C. for a firing cycle of 50 min. cooling to room temperature after firing, and polishing to obtain the ultra-fouling-resistant three-dimensional transparent glaze.
[0082] Among them, the polishing steps described in S5.6 are carried out in sequence using the following grinding heads, grinding heads composed of 5 groups of 150-mesh elastic modules, grinding heads composed of 5 groups of 600-mesh elastic modules, grinding heads composed of 5 groups of 800-mesh elastic modules, grinding heads composed of 4 groups of 1000-mesh elastic modules, grinding heads composed of 4 groups of 1200-mesh elastic modules, grinding heads composed of 5 groups of 1500-mesh elastic modules and grinding heads composed of 4 groups of 2000-mesh elastic modules. The pressure applied to the surface of the ceramic tiles by the grinding heads composed of the elastic modules is 2.0 MPa.
[0083] Comparative Example 1
[0084] This comparative example does not use modified kaolin, and the remaining steps are consistent with Example 1.
[0085] Comparative Example 2
[0086] In this comparative example, silicon carbide was not added during the kaolin modification process, and the remaining steps were consistent with those in Example 1.
[0087] Comparative Example 3
[0088] In this comparative example, only kaolin and silicon carbide are ground and mixed during the kaolin modification process, and the remaining steps are consistent with Example 1.
[0089] Comparative Example 4
[0090] This comparative example only uses a grinding head consisting of 4 groups of 2000-mesh elastic modules during the polishing process, and the remaining steps are consistent with Example 1.
[0091] The surface of the super-fouling resistant three-dimensional transparent glaze prepared in the embodiment and the comparative example was tested for wear resistance according to GB / T3810.7-2016, and the surface stain resistance was tested according to GB / T 3810.14-2016. The experimental results are summarized in the following table:
[0092] Wear resistance (level) Stain resistance (level) Example 1 5 5 Example 2 5 5 Example 3 5 5 Comparative Example 1 3 3 Comparative Example 2 4 5 Comparative Example 3 4 4 Comparative Example 4 5 3
[0093] Experimental data show that the addition of modified kaolin makes the glaze surface more wear-resistant and stain-resistant. Multiple polishing processes not only improve the surface gloss, but also effectively improve the stain resistance.
[0094] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A super stain-resistant three-dimensional transparent glaze, characterized in that: It comprises a base glaze and a super stain-resistant top glaze, wherein the base glaze has the following formula: by mass percentage, nepheline 10-25%, albite 10-15%, kaolin 5-10%, ball clay 2-5%, calcined alumina 10-15%, quartz 15-20%, potassium feldspar 15-25%, dolomite 2-4%, talc 2-5%, zinc oxide 3%; The formula of the super stain-resistant glaze is as follows: by mass percentage, 40-45% high-temperature frit, 30-40% quartz, 3-5% strontium carbonate, 3-5% zinc oxide, 10-15% modified kaolin, and 3-5% aluminum oxide; The preparation method of modified kaolin is as follows: S1.1: kaolin and silicon carbide were mixed in a mass ratio of 4:1, and ground in a ball mill at a speed of 300 r / min for 1 h to obtain a mixture A; S1.2: Dimethyl sulfoxide and dimethylformamide were mixed in a mass ratio of 2:1, and 2 wt% potassium acetate was added, and the mixture was stirred to obtain a mixed solution B. The mixture A was dispersed in the mixed solution B to obtain a solid-liquid mixture C with a mass fraction of 30%. After ultrasonic treatment for 0.5 h, the mixture was filtered to obtain a mixture D; S1.3: subjecting the mixture D to microwave radiation for 5 min at a microwave frequency of 600 MHz to obtain a mixture E; S1.4: Transfer the mixture E to a muffle furnace and heat it from room temperature to 1000°C for calcination for 3 hours. After calcination, slowly cool it to room temperature, crush and sieve it to obtain a 150-mesh solid powder, which is the modified kaolin.
2. The ultra-fouling resistant three-dimensional transparent glaze according to claim 1, characterized in that: The composition of the high-temperature frit is: Al2O3: 23.58%, SiO2: 45.47%, CaO: 16.61%, MgO: 0.45%, BaO: 1.33%, Na2O: 1.07%, K2O: 4.74%, and ZnO: 6.75%.
3. The super-fouling-resistant three-dimensional transparent glaze according to claim 1, characterized in that: The heating rate in S1.4 is 5°C / min.
4. The super-fouling-resistant three-dimensional transparent glaze according to claim 1, characterized in that: The rate of slowly cooling to room temperature in S1.4 is 3°C / min.
5. A process for preparing the ultra-fouling resistant three-dimensional transparent glaze according to any one of claims 1 to 4, characterized in that: The specific process of preparing the super-fouling-resistant three-dimensional transparent glaze is as follows: S5.1: Put the raw materials of the base glaze into a ball mill according to the formula ratio, the speed of the ball mill is 300r / min, after grinding for 1h, add 35wt% of water, 0.1wt% of sodium carboxymethyl cellulose and 0.45wt% of sodium tripolyphosphate, increase the speed of the ball mill to 400r / min, continue grinding for 8h, use a magnetic iron remover to remove iron, and obtain the base glaze E; S5.2: Put the raw materials of the super stain-resistant glaze into a ball mill according to the formula ratio, the speed of the ball mill is 300r / min, after grinding for 1h, add 35wt% of water, 0.1wt% of sodium carboxymethyl cellulose and 0.45wt% of sodium tripolyphosphate, increase the speed of the ball mill to 400r / min, continue grinding for 8h, use a magnetic iron remover to remove iron, and obtain super stain-resistant glaze F; S5.3: The surface of the green body is purged with nitrogen, and the base glaze E is poured on the surface of the green body by the pouring method. After the pouring is completed, it is allowed to stand and dry to obtain a green body G; S5.4: spraying pigment onto the surface of body G, and letting it stand to dry again to obtain body H; S5.5: pouring the super stain-resistant glaze F on the surface of the body H by a pouring method, and letting it stand to dry after pouring to obtain the body I; S5.6: placing the body I into a kiln for firing at a kiln temperature of 1140° C. for a firing cycle of 50 min. cooling to room temperature after firing, and polishing to obtain the ultra-fouling-resistant three-dimensional transparent glaze.
6. The preparation process of the super-fouling-resistant three-dimensional transparent glaze according to claim 5, characterized in that: The purge flow rate of nitrogen in S5.3 is 10 m / s.
7. The preparation process of the super-fouling-resistant three-dimensional transparent glaze according to claim 5, characterized in that: The parameters of the glazing method in S5.3 are: glazing distance 30 cm, base glaze specific gravity 1.82-1.88 g / ml, glazing amount 60 g / piece, and tile size 300*600 mm.
8. The process for preparing the ultra-fouling resistant three-dimensional transparent glaze according to claim 5, characterized in that: The spraying parameters of the pigment in S5.4 are: spraying distance 80 mm, spraying rate 60 mm / s.
9. The process for preparing the ultra-fouling resistant three-dimensional transparent glaze according to claim 5, characterized in that: The parameters of the glazing method in S5.5 are: glazing distance 30 cm, super stain-resistant glaze specific gravity 1.82-1.87 g / ml, glazing amount 70 g / piece, and tile size 300*600 mm.
10. The process for preparing the ultra-fouling resistant three-dimensional transparent glaze according to claim 5, characterized in that: The polishing steps described in S5.6 are carried out in sequence using the following grinding heads, grinding heads composed of 5 groups of 150-mesh elastic modules, grinding heads composed of 5 groups of 600-mesh elastic modules, grinding heads composed of 5 groups of 800-mesh elastic modules, grinding heads composed of 4 groups of 1000-mesh elastic modules, grinding heads composed of 4 groups of 1200-mesh elastic modules, grinding heads composed of 5 groups of 1500-mesh elastic modules and grinding heads composed of 4 groups of 2000-mesh elastic modules. The pressure applied to the surface of the ceramic tiles by the grinding heads composed of the elastic modules is 1.3 to 2.0 MPa.
Citation Information
Patent Citations
High-white ground glaze, wear-resistant transparent glaze, wear-resistant full-polished glaze ceramic tile and preparation method
CN114920457A
Ceramic tile with three-dimensional decorative effect and preparation process thereof
CN114920586A